Third International Conference on Intelligent Computing and Human-Computer Interaction (ICHCI 2022) 2023
DOI: 10.1117/12.2655940
|View full text |Cite
|
Sign up to set email alerts
|

Improved YOLOv5 for skeleton-based classroom behavior recognition

Abstract: Classroom behavior is an important criterion for evaluating instructional efficacy. In comparison to other behaviors, the challenge of classroom behavior detection is primarily influenced by ambient light variables and the presence of too many targets to recognize, resulting in missed detection. Recent research has demonstrated that information about the human skeleton can be used to identify classroom conduct. As a result, we present an enhanced yolov5-based skeletal recognition system for detecting class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Traditional human observation methods are not capable of quickly and accurately capturing a large number of student classroom behaviors. However, numerous studies and practices have shown that using deep learning models for classroom behavior analysis is an effective way [1][2][3][4]. At the same time, some scholars have provided great research ideas for behavior detection by constructing virtual scenes through Digital Twin technology to obtain relevant information [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional human observation methods are not capable of quickly and accurately capturing a large number of student classroom behaviors. However, numerous studies and practices have shown that using deep learning models for classroom behavior analysis is an effective way [1][2][3][4]. At the same time, some scholars have provided great research ideas for behavior detection by constructing virtual scenes through Digital Twin technology to obtain relevant information [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, a drawback of their method was its reliance on addressing the partial blockage of numerous human targets, and the inclusion of the skeletal (2S-AGCN) module resulted in slower inference and detection times. In our proposed approach, we aimed to strike a balance between model speed and accuracy by modifying all parts of the model [12].…”
Section: Introductionmentioning
confidence: 99%